Draft Eighth Five Year Plan 1990-95 Volume : X Hill Areas Government of Assam - Planning Commission (Planning Commission, 1990)
The autonomous hills districts of Assam, i.e. Karbi Aaglong and North Cachar Hills comprises nearly 19.38% of the total Geographical area of the state and 3.11 % of the total population of Assam. The hill areas of Assam is the most backward 'in all respects due to geographical isolation, poverty, poor communication, lack of general infrastructure, social services etc.
Government of Assam, Development Commissioner for Hill Areas